What is useful to know post COVID-19? - Gianvincenzo Zuccotti; Valeria Calcaterra (Elsevier, 2023)
About 60-70 % of infected children show no symptoms, and among those with symptoms, 90 % experience mild to moderate infections, though severe cases have been reported, with a mortality rate of 0.1 % among pediatric patients. Despite limited severe manifestations in the acute phase, two main long-term complications of COVID-19 have been observed in the pediatric population: Multisystem Inflammatory Syndrome in Children (MIS-C) and Long COVID. MIS-C and Long COVID outcomes are generally better than those of adults. However, the pandemic has exacerbated existing societal inequities, raised adolescents' social awareness, and influenced short- and long-term plans for their education and careers. To support adolescents in navigating an uncertain future, efforts should focus on strategies for their well-being and future prospects.